PENDIDIKAN GENDER DALAM ISLAM: Studi Analisis Nilai-nilai Kesetaraan Gender dalam Pelajaraan PAI di SD Ma’arif Ponorogo - Nanik Setyowati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
The research that the authors do is focused on the value of gender equality contained in the material of PAI and how to implement it in a learning process. The methode used is descriptive-qualitative. From the research conducted found that 1). There is still a gender bias of men and women who consciously or unconsciously have been presented in the PAI textbooks used in SD 2). Gender Equality in PAI Learning has no learning process or treatment to students outside of gender biased class 3). Teachers' Efforts in Embedding the Value of Gender Equality through learning is To increase insight and raise awareness about gender equality, Action and gender anti-discrimination in PAI learning process and out-of-class activities, Be sensitive to gender issues both in learning and in the use of material books PAI.